Implementation of Semi-Destructive Mechanical Testing Techniques for Quantification of Irradiated NPP Components Materials Operational Degradation. (2015) - Kopřiva, R.; Falcník, M.; Eliášová, I.; Siegl, J.
Abstract: In the terms of nuclear power plant operational life management, current trend of components lifetime extension requires precise and credible information of structural material degradation. Present-day standard conventional methods of mechanical testing are usually based on the use of large specimens and higher consumption of testing material, whose availability and volume is often limited. For determination of material properties, sampling of the necessary volume of material is in most cases connected with affecting the integrity or even destruction of the assessed component. Moreover, several components are not usually covered surveillance programs, e.g. reactor pressure vessel internals. Innovative testing methods of Small Punch Testing (SPT) and Automated Ball Indentation Test (ABIT) are based on the determination of material properties from miniaturized testing specimens and their semi-destructive approach is very promising for the possibility of present data base of irradiated materials testing results enlargement and enable the option of component in- situ testing (ABI testing). Presentation is focused on description of the process of employment of these techniques in the process of irradiated NPP materials testing and evaluation at the accredited hot cell testing laboratory of UJV Rez, Mechanical Testing Department. Comparison with testing results from conventional mechanical testing methods is also depicted.